Early and Late Cardiovascular and Metabolic Responses to Mixed Wine: Effect of Drink Temperature - Sarafian, Delphine; Maufrais, Claire; Montani, Jean-Pierre (Frontiers in Physiology, 2018)
Abstract (341 words) Aim: Red wine is usually ingested as an unmixed drink. However, mixtures of wine with juices and/or sucrose (mixed wine) are becoming more and more popular and could be ingested at either cold or hot temperature. Although the temperature effects on the cardiovascular system have been described for water and tea, with greater energy expenditure and lower cardiac workload with a colder drink, little information is available on the impact of temperature of alcoholic beverages on alcoholaemia and cardiometabolic parameters. The purpose of the present study was to compare the acute cardiovascular and metabolic changes in response to mixed wine ingested at a cold or at a hot temperature. Methods: In a randomized crossover design, fourteen healthy young adults (7 men and 7 women) were assigned to cold or hot mixed wine ingestion. Continuous cardiovascular, metabolic and cutaneous monitoring was performed in a comfortable sitting position during a 30-min baseline and for 120 min after ingesting 400 mL of mixed wine, with the alcohol content adjusted to provide 0.4g ethanol/kg of body weight and drunk at either cold (3°C) or hot (55°C) temperature. Breath alcohol concentration was measured intermittently throughout the study. Results: Overall, alcoholaemia was not altered by drink temperature, with a tendency toward greater values in women compared to men. Early responses to mixed wine ingestion (0-20 min) indicated that cold drink transiently increased mean blood pressure, cardiac vagal tone and decreased skin blood flow whereas hot drink did not change blood pressure, decreased vagal tone and increased skin blood flow. Both cold and hot mixed wine led to increases in energy expenditure and reductions in respiratory quotient. Late responses (60-120 min) led to similar cardiovascular and metabolic changes at both drink temperatures. Conclusion: The magnitude and/or the directional change of most of the study variables differed during the first 20 min following ingestion and may be related to drink temperature. By contrast, late changes in cardiometabolic outcomes were similar between cold and hot wine ingestion, underlying the typical effect of alcohol and sugar intake on the cardiovascular system.